Neurocognitive follow-up in adult siblings with Phelan-McDermid syndrome due to a novel SHANK3 splicing site mutation - Kankuri-Tammilehto Minna; Sauna-aho Oili; Arvio Maria (WILEY, 2022)
Background: Phelan-McDermid syndrome (PMD) is usually not only caused by 22q13.3 deletion but also pathogenic variants (mutations) of SHANK3 gene. PMD is characterized by global intellectual disability, severely delayed or absent speech, and features of autism spectrum disorder and susceptibility to psychotic behavior. Here, we describe a neurocognitive follow-up and genetic etiology for two siblings with PMD.Method: Comparative genomic hybridization (CGH) array test was normal and no 22q13.3 deletion was observed. For this reason, whole exome sequencing (WES) analyzed the siblings' and the parents' DNA sample.Results: The results of the siblings strongly suggest that the SHANK3 gene variant c.2313+1G>A is pathogenic and PMD can be inherited from a mosaic father for this gene variant. Both siblings learned new skills until puberty but experienced a neuropsychiatric disaster after the age of 14 years experienced neurocognitive decline and it was sharp for one of the siblings.Conclusion: The long-term observations are sparse in PMD and SHANK3 mutations. This is the neurocognitive follow-up from childhood to middle ages, where a sharp neurocognitive decline was observed. We conclude that progressive neuropsychiatric symptoms in adolescence are a universal clinical clue for PMD diagnosis and an underlying SHANK3 splicing site mutation.